2013
DOI: 10.1093/humrep/det105
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically healthy polycystic ovary syndrome (MH-PCOS) and metabolically unhealthy polycystic ovary syndrome (MU-PCOS): a comparative analysis of four simple methods useful for metabolic assessment

Abstract: The results will facilitate the early recognition of cardiometabolic risk in women with PCOS before they develop overt metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
0
31
0
3
Order By: Relevance
“…Elevated VAI was defined as VAI O1.675 as described previously (11). Insulin resistance was estimated using the homeostatic model assessment-insulin resistance (HOMA-IR) and was assumed for levels O2.5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated VAI was defined as VAI O1.675 as described previously (11). Insulin resistance was estimated using the homeostatic model assessment-insulin resistance (HOMA-IR) and was assumed for levels O2.5.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative insulin sensitivity check index (QUICKI) was used for estimation of insulin sensitivity (11). We further calculated insulin sensitivity index Matsuda (ISI (Matsuda)) as an insulin sensitivity index that reflects a composite estimate of hepatic and muscle insulin sensitivity determined from OGTT data ðISI ðMatsudaÞ Z 10 000=OððFG !…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, this phenotype is said to have the lowest cardiovascular risk compared to other phenotypes (2). Amato et al (45) conducted a study in order to verify a method for distinguishing the metabolic health of women of reproductive age with PCOS. The visceral adiposity index is suggested as an easy and successful method for the assessment of metabolically unhealthy women and the detection of cardiometabolic risk factors.…”
Section: Pathogenesis Of Metabolic Syndrome In Adolescent Pcos Womenmentioning
confidence: 99%
“…10 Recent studies evaluated VAI in women with PCOS and reported that VAI correlated with insulin resistance, differentiate the "metabolically healthy polycystic ovary syndrome" from the "metabolically unhealthy polycystic ovary syndrome" Also VAI replace visceral CT scan as a marker for visceral adiposity. [11][12][13] VAI is considered a predictor of clinical severity and therapeutic outcome of PCOS.…”
Section: Introductionmentioning
confidence: 99%